An Online Interval-Based Inertial Navigation System for Control Purposes of Autonomous Boats - Le Bars, Fabrice; Sanchez , Robin; Jaulin , Luc; Rohou , Simon; Rauh , Andreas (Frontiers in Control Engineering, 2022)
Interval analysis is a numerical tool classically used for solving nonlinear equations in a guaranteed way. It has been shown that it can be used to build reliable nonlinear state estimators for dynamical systems. Numerous simulations inspired from real-life applications have shown the applicability of the approach. This paper proposes to implement an interval-based INS (Inertial Navigation System) in an actual robot to estimate its orientation and position. It shows that some types of outliers can be naturally handled by the fusion algorithm, while the resulting controller can be both fast and reliable. Experiments with an actual autonomous boat conclude this article.